Optimasi management lab bagi guru IPA di Kabupaten Enrekang - Andi Asmawati Aziz; Andi Citra Pratiwi; Yusnaeni Yusuf (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
In the context of education in schools, laboratories serve to facilitate learning with practical methods that can provide learning experiences for students to interact with practical tools and materials, and also to do direct observation. School laboratories need a special attention, especially the science laboratory which covers the fields of Physics, Chemistry, and Biology, since it is a place to improve students' science process skills. Field observations show that there are still many laboratories that do not meet the standards, especially school laboratories in Enrekang Regency. The obstacles experienced by most schools are the lack or absence of laboratory staff who help to manage laboratory activities properly, the lack of laboratory equipment that can be used, and also the damage of laboratory equipment. Accordingly, this activity was aimed to improve the ability of science teachers in conducting laboratory management and in improving laboratory management in schools. The method implemented was a study of the management of science laboratories in several schools in Enrekang Regency through training on laboratory management and the use of online media as an alternative method for carrying out practical activities for students.